PERAN MEDIASI KNOWLEDGE SHARING: PERCEIVED SELF EFFICACY DAN PERCEIVED ENVIRONMENTAL SUPPORT TERHADAP KINERJA KARYAWAN BPJS KETENAGAKERJAAN CABANG CILACAP - Sofyantoro, Fiqih; Lukiastuti, Fitri; Djou, Laurentius Dominicus Gadi (FACULTY OF ECONOMICS AND BUSINESS FLORES UNIVERSITY, 2025)
This study examines how self-belief and environmental support affect employee performance with knowledge sharing as a mediating variable. The research was conducted at BPJS Ketenagakerjaan Cilacap Branch by involving all 65 employees as samples through saturated sampling technique. Data analysis used the Partial Least Square (PLS) method with the help of SmartPLS software. The results showed several important findings: self-confidence and environmental support each have a significant effect on knowledge sharing. Both variables also have a significant effect on employee performance. In addition, knowledge sharing was shown to have a significant effect on employee performance. Interestingly, knowledge sharing acts as a mediator in the relationship between self-confidence and employee performance, as well as between environmental support and employee performance.